Perlindungan Konsumen terhadap Kelangkaan Produk Non Pokok Akibat Penimbunan yang Dilakukan oleh Pelaku Usaha - Satria Aldyan Firmanda; Iwan Erar Joesoef (Wajah Hukum, 2021)
In 2020 Walls Indonesia re-launched their legendary product, "Viennetta" Ice Cream which was famous in the 90s. but this is misused by bad people who are not responsible for their own interests. They took advantage of the public's enthusiasm for the return of the legendary product from Walls Indonesia, namely Viennetta Ice Cream by hoarding these items and selling them at a higher price. The regulations regarding consumer protection against hoarding of goods have received protection from the Ministry of Trade in the Regulation of the Minister of Trade Number 20/M-DAG/PER/3/2017 concerning Registration of Business Actors in the Distribution of Staple Needs, but unfortunately this regulation only applies to basic goods. Therefore, this study aims to educate consumers in order to know their rights as consumers and so that the government can re-discuss regulations regarding stockpiling of goods so that they can be expanded not only to basic necessities by using the juridical normative research method and using a statutory approach, the authors get the results of this research that consumers can still get legal protection against the scarcity of a non-basic item by using the Trade Law, the Consumer Protection Law, and the Business Competition Law..